Comparison of skeletal and dental changes between 2-point and 4-point rapid palatal expanders - Lamparski, Don G.; Rinchuse, Daniel J.; Close, John M.; Sciote, James J. (American journal of orthodontics and dentofacial orthopedics, 2003)
Rapid palatal expansion has been a clinically accepted technique used by orthodontists for over 100 years. Its primary goal is to maximize orthopedic and minimize orthodontic movements of teeth. Historically, this was best accomplished by including 4 teeth in the appliance. However, including more teeth makes construction and insertion more difficult. The appliance also is less comfortable for patients and hinders oral hygiene. The 4-point hyrax expander can be modified by removing the 2 anterior wires, creating a 2-point expander between the first molars only. The purpose of this study was to determine the difference, if any, between midpalatal suture separation and dental expansion produced between 2-point and 4-point palatal expanders. Thirty subjects between the ages of 6 and 16 years were randomly assigned to either the 2-point (n = 15) or the 4-point group (n = 15). The groups were compared on dental and radiographic landmarks. The groups showed no statistical differences in total molar cusp width, molar gingival width, canine cusp width, canine gingival width, or diastema width. There were slight differences in arch perimeter and midpalatal suture separation. The results of this study showed that the 2-point appliance produced similar effects on the midpalatal suture and the dentition as did the 4-point appliance. It might therefore be considered instead of the 4-point appliance to successfully produce adequate skeletal and dental expansion. (Am J Orthod Dentofacial Orthop 2003;123:321-8)